Abkhazia: preliminary socio-political results of 2017 - А. Yu. Skakov; V. М. Мukhanov (Международная аналитика)
The article analyses the political situation in Abkhazia in 2017, namely, the activities of the government and the opposition, parliamentary elections, their results and the power balance in the new legislative body. It also studies the existence of the third force, which is a topical issue in Abkhazian society. The author examines the grave socio-economic situation in the Republic this year, which continues to worsen, and comes to the conclusion that the reasons for this deterioration are the failure of the tourist season and catastrophic Abkhazian reputation losses. Besides, the article scrutinizes the main problems in Russian-Abkhazian relations, the aggravation of the crime situation in Abkhazia, the current church footing (splits in church congregations) and issue regarding the Gali residents’ status.